International Order in Historical East Asia: Tribute and Hierarchy Beyond Sinocentrism and Eurocentrism. (2020) - Kang, David C.
Abstract: IR theorizing about international order has been profoundly, perhaps exclusively, shaped by the Western experiences of the Westphalian order and often assumes that the Western experience can be generalized to all orders. Recent scholarship on historical East Asian orders challenges these notions. The fundamental organizing principle in historical East Asia was hierarchy, not sovereign equality. The region was characterized by hegemony, not balance of power. This emerging research program has direct implications for enduring questions about the relative importance of cultural and material factors in both international orders and their influence on behavior—for describing and explaining patterns of war and peace across time and space, for understanding East Asia as a region made up of more than just China, and for more usefully comparing East Asia, Europe, and other regions of the world.